An ambruticin-sensing complex modulates Myxococcus xanthus development and mediates myxobacterial interspecies communication - Francisco Javier Marcos-Torres (Nature Portfolio, 2020)
Starvation induces cell aggregation and formation of spore-containing fruiting bodies in the bacterium Myxococcus xanthus. Here, the authors show that a different myxobacterial species produces a compound that inhibits the development of fruiting bodies in M. xanthus, by affecting the function of histidine kinases and major regulators.